The Influence of Growth Opportunity, Capital Structure, Dividend Policy on Firm Value in Agricultural Sector Companies in the Plantation Sub-Sector - Setiyani, Ayu Fera; Hariasih, Misti (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to examine the effect of growth opportunity, capital structure, dividend policy on firm value. The approach used in this research is a quantitative approach. The population in this study are plantation sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling method. The sample in this study were 6 companies listed on the Indonesia Stock Exchange in 2015-2019. The data used in this study is secondary data taken from the Indonesia Stock Exchange. Data analysis uses Eviews 9 analysis with the aim of testing growth opportunity (X1), capital structure (X2) and dividend policy (X3) on firm value (Y). The results of this study indicate that there is a significant influence between growth opportunity, capital structure, dividend policy on firm value. Likewise, the variables of growth opportunity, capital structure, dividend policy have a simultaneous effect on firm value.